2022
DOI: 10.1177/23259582221084885
|View full text |Cite
|
Sign up to set email alerts
|

HIV Care in the Times of COVID-19 Pandemic in Urban South Gujarat: An Operational Overview

Abstract: In India, the nationwide lockdown was implemented from March to May 2020 due to COVID-19 pandemic. As of March 2020, there were 13.08 lakh PLHIV availing ART free of cost from Government run ART centres, To maintain the continuum of care, National AIDS Control Programme (NACP) of India adopted Multi Months Dispensation (MMD) through ART centres and Community Dispensation of ART through the various Targeted Interventions (TI) and Community Based Organizations (CBO). A mixed methods study was designed, with desk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Service providers utilised different delivery approaches to overcome barriers to clients accessing ART during the COVID-19 pandemic, ensuring people on ART stayed supplied with their medications. For example, HIV service providers delivered ART to community dispensaries, community health centres, community pharmacies, and other community-based organisations [ 54 , 57 , 61 , 65 , 66 ]. Several services utilised their existing network of community-based health workers to deliver ART [ 52 , 55 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Service providers utilised different delivery approaches to overcome barriers to clients accessing ART during the COVID-19 pandemic, ensuring people on ART stayed supplied with their medications. For example, HIV service providers delivered ART to community dispensaries, community health centres, community pharmacies, and other community-based organisations [ 54 , 57 , 61 , 65 , 66 ]. Several services utilised their existing network of community-based health workers to deliver ART [ 52 , 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen studies reported on how HIV/AIDS organisations maintained access to ART during the pandemic by expanding their ART dispensing points. This included developing community ART dispensing strategies, setting up primary care outreach points where clients could collect their medications, decentralising ART distribution to dispensaries, dispensing through community-based organisations [ 52 , 58 , 61 , 64 , 65 , 67 ], and expanding or initiating multi-month dispensing [ 51 , 53 , 54 , 60 , 62 , 66 , 69 ]. For example, HIV service providers in Uganda utilised community drug distribution points to take ART closer to clients and facilitate access [ 69 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…En Inde, une étude mixte a réalisé l'analyse documentaire quantitative des données programmatiques et des entretiens qualitatifs approfondis avec 250 PVVIH et 15 soignants des PVVIH. L'interruption des services de laboratoire pour le dépistage du VIH et le faible recours des PVVIH aux services de prise en charge ont été observés (Samudyatha et al, 2022). Au Guatemala, Medina et al (2021) ont observé une baisse de 54,7% pour le dépistage du VIH et une augmentation de 10,7% des décès dus aux infections opportunistes pendant la COVID-19.…”
Section: Baisse De L'utilisation Des Services Vihunclassified